UNUSUAL MASSIVE RECRUITMENT OF THE REEF FISH CTENOCHAETES STRIGOSUS (BENNET) (PERCIFORMES: ACANTHURIDAE) TO THE MINICOY ATOLL AND ITS SIGNIFICANCE - Pillai, C S Gopinatha; Mohan, Madan; Kunhikoya, K K (Indian Journal of Fisheries, 2011)
A sudden influx, and subsequent settlement, of C. strigosus in enormousnumbers in the lagoon and on reef flats of Minicoy island, where, but for a coupleof specimens dealt with by Jones and Kumaran (1980, this species was almostunknown, is reported. The fish, ranging in length from 50 to 82 mm, which hadbeen obviously leading thus far a pelagic life, were in stages past postlarval, andwere already in the process of metamorphosing into adult, with gonads in stagesup to Stage III maturity.